Accountability Analysis of Productive Zakat Fund Management at the National Zakat Amil Agency Baznas, Meranti Islands District - Kiki Candri; Sri Rahmany; Susilawati; Een Erlina; Saiful Bahri; Mela Artika (International Journal of Sustainable Applied Sciences, 2024)
Implementation of accountability at the national zakat amil agency (BAZNAS) Meranti Islands district in the management of productive zakat funds. The aim of implementing accountability in the management of zakat funds is to create trust in the parties involved in the management and as a form of responsibility for the trust given. The type of data in this research is descriptive qualitative using primary data, namely data obtained directly from the research object. The data collection technique is using interview and documentation techniques. The research results illustrate that BAZNAS Meranti Islands district has not fully implemented accountability in the management of zakat funds.  In implementing BAZNAS accountability for the Meranti Islands district, is done by making financial reports and conducting audits. In preparing the financial reports, BAZNAS, Meranti Islands Regency has implemented the guidelines based on PSAK No. 109, however, it is still not fully implemented. This is because, in the management of BAZNAS zakat  funds  in  Meranti Island Regency, there is a lack of human resources as managers appropriate to their field, a lack of financial